2004
DOI: 10.1002/gcc.20135
|View full text |Cite
|
Sign up to set email alerts
|

β‐Catenin (CTNNB1) gene amplification: A new mechanism of protein overexpression in cancer

Abstract: beta-Catenin nuclear translocation is frequently observed in different types of malignancies, including gastric cancer. In gastric cancer, however, the molecular mechanisms leading to accumulation of this protein in the nucleus remain unknown. In this setting, beta-catenin (CTNNB1) mutations have been reported, but studies of mutation frequency have yielded conflicting results. Mutations or silencing of other partners of beta-catenin (i.e., APC and AXIN) are also considered rare genetic events in gastric tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…A recent in situ hybridization analysis revealed CTNNB1 gene amplification in KatoIII (Suriano et al, 2005), and we found boosted TCF/LEF transcriptional activity in the same cells. Thus, CTNNB1 amplification appears to be one mechanism by which b-catenin can be overexpressed, but the frequency of this change in primary GCs is quite low (1 of 49 patients) (Suriano et al, 2005).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A recent in situ hybridization analysis revealed CTNNB1 gene amplification in KatoIII (Suriano et al, 2005), and we found boosted TCF/LEF transcriptional activity in the same cells. Thus, CTNNB1 amplification appears to be one mechanism by which b-catenin can be overexpressed, but the frequency of this change in primary GCs is quite low (1 of 49 patients) (Suriano et al, 2005).…”
Section: Discussionsupporting
confidence: 75%
“…A GGA-GAA transition at codon 34 (G34E) in CTNNB1 was found in AGS cells (Caca et al, 1999), and an ACC-GCC change at codon 41 (T41A) in CTNNB1 was detected in SNU638 cells (Ku and Park, 2005). In addition, CTNNB1 gene amplification was recently demonstrated in KatoIII cells (Suriano et al, 2005). The two cell lines with APC mutations and KatoIII cells all showed typical features of constitutive activation of Wnt signaling, that is, dephosphorylation and nuclear accumulation of b-catenin and upregulation of TCF/ LEF-regulated transcription (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PLA2G2A expression in GC cells seems to be highly correlated with constitutive activation of the Wnt signaling pathway. Furthermore, supporting this model, AGS cells possess a gain of function phosphorylation site mutation in the CTNNB1 (h-catenin) gene (13), and Kato III cells have both a genomic amplification of the CTNNB1 gene and a promoter methylation of APC, a negative regulator of Wnt signaling (14). Similarly, we found that YCC3 cells exhibited CTNNB1 gene amplification and high CTNNB1 mRNA expression levels ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 57%
“…About 85% of GCs can be categorized as the IT or DT histologic type based on the Lauren classification, and the remaining GCs usually are comprised of a mixture of IT and DT and are thus classified as MT. Little is known regarding the molecular alterations in MT carcinomas, except for mutation of the E-cadherin gene (CDH1) [27] and the β-catenin gene (CTNNB) [28]. The morphological differences between IT and DT carcinomas can be attributed, at least in part, to differences in CDH1 expression.…”
Section: Discussionmentioning
confidence: 98%